Visualizing spatial distribution of small molecules in the rhubarb stalk (Rheum rhabarbarum) by surface-transfer mass spectrometry imaging. (July 2017) - Nizioł, Joanna; Sekuła, Justyna; Ruman, Tomasz
Abstract: Laser desorption/ionization mass spectrometry imaging (LDI-MSI) with gold nanoparticle-enhanced target (AuNPET) was used for visualization of small molecules in the rhubarb stalk ( Rheum rhabarbarum L.). Analysis was focused on spatial distribution of biologically active compounds which are found in rhubarb species. Detected compounds belong to a very wide range of chemical compound classes such as anthraquinone derivatives and their glucosides, stilbenes, anthocyanins, flavonoids, polyphenols, organic acids, chromenes, chromanones, chromone glycosides and vitamins. The analysis of the spatial distribution of these compounds in rhubarb stalk with the nanoparticle-rich surface of AuNPET target plate has been made without additional matrix and with minimal sample preparation steps. Graphical abstract: The distribution of biologically active compounds in the rhubarb stalk was investigated by laser desorption/ionization mass spectrometry imaging (LDI MSI) with gold nanoparticle-enhanced target (AuNPET). Highlights: Nanoparticle enhanced target in MS imaging of plant cross-section. Localization of biologically active compounds in rhubarb stalk ( Rheum rhabarbarum ). Compilation of knowledge of the most important compounds in rhubarb.